Ductility Ratio and Toughness Index of Reinforced Concrete Slabs Subjected to High Temperature - M, Ahmed Heidayet; Qarani, Omer (Sulaimani Journal for Pure and Applied Sciences, 2002)
Ductility ratio and toughness index were studied for two -way reinforced concrete slabs subjected to high temperature and cooling. . Empirical equations were developed to predict the ductility ratio and toughness index ( in terms of temperature and reinforced ratio) of such slabs under uniformly distributed load . These proposed equation gave good agreement when compared with the experimental results, with a correlation factor for ductility ratio and toughness index of 0.94 and 0.95 ,respectively.
Keywords: slabs; ductility ratio; toughness index; high temperature; twoway slob; ductility; reinforced concrete